Constituting the un-American atheist: Eisenhower's theistnormativity and the negation of American atheists - Lee, Kristina M., author; Anderson, Karrin Vasby, advisor; Prasch, Allison, committee member; Cloud, Doug, committee member (Colorado State University. Libraries, 2018)
During the Cold War, President Eisenhower used civil religion and what Philip Wander calls prophetic dualism to construct an image of the American people. In doing so he excluded atheists from his description of the American citizenry. In order to understand how atheists fit into the national imagination inspired by President Eisenhower, this thesis explores how Eisenhower talked explicitly and implicitly, through rhetorical omission, about atheists. I argue that President Eisenhower framed atheists as un-American during his presidency, which contributed to a negative perception of atheists that is still prevalent in modern American society. This thesis also calls on scholars to be more mindful of how the theist-normativity promoted in American society marginalizes American atheists, both historically and today.
Keywords: civil religion; Eisenhower; theist-normativity; atheist; prophetic dualism; Cold War